Решите уравнения :
6(x+1)^2+2(x-1)(x^2+x+1)-2(x+1)^3=32
5x(x-3)^2-5(x-1)^3+15(x+2)(x-2)=15
(x+2)^3-x(3x+1)^2+(2x+1)(4x^2-2x+1)=42

^2=квадрат
^3=куб

1

Ответы и объяснения

2014-01-26T19:49:22+04:00
1.6(x+1)^2+2(x-1)(x^2+x+1)-2(x+1)^3=32
   6(х²+2х+1)+2(х³-1)-2(х³+3х²+3х+1)-32
   6х²+12х+6+2х³-2-2х³-6х²-6х-2=32
   6х-4=32
   6х=36
   х=6;
2.5x(x-3)^2-5(x-1)^3+15(x+2)(x-2)=5
   5х³-30х²+45х-5х³+15х²-15х+5+15х²-60=5
   45х-15х-55=5
   30х=60
   х=2;
3.(x+2)^3-x(3x+1)^2+(2x+1)(4x^2-2x+1)=42
   х³+6х²+12х+8-х(9х²+6х+1)+(8х³+1)=42
   х³+6х²+12х+8-9х³-6х²-х+8х³+1=42
   11х=33
    х=3.